LIVING QUR’AN DI MEDIA SOSIAL: RESEPSI Q.S AL-ASHR (1-3) DALAM FILM INSPIRASI “AL-QUR’AN MERINDUKANMU” PADA GONTOR TV - Anggraini, Tri Faizah (Living Islam: Journal of Islamic Discourses, 2024)
The study of the living Qur'an has now spread to cyberspace. The living Qur'an, which is generally synonymous with practical phenomena in real life, does not prevent the virtual world from taking part in representing the practice of the living Qur'an in the world of cinema. The same thing happened in the film "Al-Qur'an Missing You". This inspirational short film, which aired with a duration of 19:23 seconds, succeeded in attracting an audience of 23,113. This research aims to find receptions that have been classified by Ahmad Rafiq in the film "Al-Qur'an Missing You". To achieve this goal, this research uses a qualitative research method with a descriptive-analytic approach while introducing Ahmad Rafiq's version of the living Qur'an theory as the basis for data analysis. By referring to the research process, this research found that exegetical reception, aesthetic reception and functional reception were found in the film "Al-Qur'an Missing You". By providing specific efforts, the exegetical reception is realized in Ayah's interpretation of surah al-Ashr verses 1-3, the aesthetic reception is represented in Alif's pattern of reading the Qur'an in tartil and the functional reception is from the informative aspect which is indicated by the narrative knowledge of groups of people The losers are those who abandon good deeds. Meanwhile, functional reception from the performative aspect can be seen in Alif's religious play, which begins to neutralize the reading of the Qur'an in his activities by relying on his understanding of surah al-Ashr 1-3. Keywords: Living Quran, Reception; Inspiration Film, Gontor TV   Kajian living qur’an kini merambah ke dunia maya. Living qur’an yang umumnya identik dengan fenomena praktikal di kehidupan nyata, tak menghalangi dunia maya untuk turut andil merepresentasikan praktik living qur’an di dunia perfilman. Hal yang sama terjadi pada film “Al-qur’an Merindukanmu”. Film pendek inspirasi yang tayang dengan durasi 19:23 detik ini berhasil menggait penonton sebanyak 23.113. Penelitian ini bertujuan untuk menemukan resepsi yang telah diklasifikasikan oleh Ahmad Rafiq sekaligus mencari proses transmisi dan transformasi pada film “Al-qur’an Merindukanmu”. Untuk mencapai tujuan tersebut, penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif-analisis sekaligus mengintrodusir teori living qur’an versi Ahmad Rafiq sebagai basis analisa data. Dengan mengacu pada proses penelitian tersebut, penelitian ini menemukan titik temu bahwa resepsi eksegesis, resepsi estetis dan resepsi fungsional terdapat dalam film “Al-qur’an Merindukanmu”. Dengan memberikan upaya spesifikasi, resepsi eksegesis terwujud pada penafsiran Ayah terhadap surah al-Ashr ayat 1-3, resepsi estetis terrepresentasi pada pola bacaan al-Qur’an Alif secara tartil dan resepsi fungsional dari aspek informatif yang terindikasi pada pengetahuan narasi golongan orang-orang yang merugi adalah golongan yang meninggalkan amal sholih. Sementara resepsi fungsional dari aspek performatif terlihat pada lakon beragama Alif yang mulai menetralisir dengan bacaan qur’an dalam aktivitasnya dengan bersandar pada pemahamannya terhadap surah al-ashr 1-3.   Keyword:  Living Quran, Resepsi; Film Inspirasi, Gontor TV